2019
DOI: 10.1038/s41598-019-52879-y
|View full text |Cite
|
Sign up to set email alerts
|

Freezing method for rock cross-cut coal uncovering I: Mechanical properties of a frozen coal seam for preventing outburst

Abstract: A comprehensive technology is proposed to realize fast and safe rock cross-cut coal uncovering (RCCCU) based on artificial freezing engineering method. This comprehensive technology includes four steps, namely, drilling a borehole, wetting the coal body by water injection, gas drainage and freezing the coal seam by liquid nitrogen injection. In this paper, the compressive strength, tensile strength and shear strength of frozen coal specimens are tested to obtain the mechanical parameters of the specimen. Then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Jia et al [8] concluded that the tensile strength of saturated coal and rock increased below 0°C. Yue et al [9] concluded that as the temperature of coal decreases, the compressive strength and tensile strength increase linearly. Li et al [10] revealed that the strength of ice crystals, the strength of the particle mixture, the friction strength between blocks, and the occlusal strength are the main factors affecting the uniaxial compressive strength of the frozen soil rock mixture and the ice crystals improve the bearing capacity and ductility.…”
Section: Introductionmentioning
confidence: 99%
“…Jia et al [8] concluded that the tensile strength of saturated coal and rock increased below 0°C. Yue et al [9] concluded that as the temperature of coal decreases, the compressive strength and tensile strength increase linearly. Li et al [10] revealed that the strength of ice crystals, the strength of the particle mixture, the friction strength between blocks, and the occlusal strength are the main factors affecting the uniaxial compressive strength of the frozen soil rock mixture and the ice crystals improve the bearing capacity and ductility.…”
Section: Introductionmentioning
confidence: 99%
“…e strength of frozen coal body is indeed greatly improved, especially as coal body contains a certain amount of water [22,23]. Yue et al [24] tested the compressive strength, tensile strength, and shear strength of frozen coal specimens and obtained the mechanical parameters of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…It will not only cause a serious malignant accident of mass casualties, but also result in huge property losses (Pan et al, 2020;Wang et al, 2019). Especially, for rock crosscut coal uncovering (RCCU), although the times of coal-gas outbursts is less, the outburst intensity is larger, and more than 80% of the super large coal-gas outbursts occur in the process of RCCU (Yang et al, 2021;Yue et al, 2019aYue et al, , 2019b. Moreover, with the increase of coal-mining depth, the in-situ stress, temperature and gas pressure gradually increase, which increases the risk of RCCU and seriously threatens safe and efficient mining (Wang et al, 2013;Yu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%